2018
DOI: 10.1042/cs20180040
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibition with alirocumab reduces lipoprotein(a) levels in nonhuman primates by lowering apolipoprotein(a) production rate

Abstract: Therapeutic antibodies targeting proprotein convertase subtilisin kexin type 9 (PCSK9) (e.g. alirocumab) lower low-density lipoprotein cholesterol (LDL-C) and lipoprotein (a) [Lp(a)] levels in clinical trials. We recently showed that PCSK9 enhances apolipoprotein(a) [apo(a)] secretion from primary human hepatocytes but does not affect Lp(a) cellular uptake. Here, we aimed to determine how PCSK9 neutralization modulates Lp(a) levels Six nonhuman primates (NHP) were treated with alirocumab or a control antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…A small kinetic study suggested that the reduction in plasma Lp(a) levels following alirocumab treatment was due to the increased clearance of Lp(a)‐apo(a), suggestive of a LDLR‐mediated clearance of Lp(a) from the circulation . A better powered human kinetic study and a kinetic study using non‐human primates, however, showed that the production rate but not the clearance of Lp(a)‐apo(a) was significantly reduced following evolocumab or alirocumab treatment, respectively . These data concur with the observation that statin treatment has no effect on Lp(a) levels despite a strongly up‐regulation of hepatic LDLR levels …”
Section: Efficacy Of Pcsk9 Inhibitors In T2dm Patientssupporting
confidence: 66%
“…A small kinetic study suggested that the reduction in plasma Lp(a) levels following alirocumab treatment was due to the increased clearance of Lp(a)‐apo(a), suggestive of a LDLR‐mediated clearance of Lp(a) from the circulation . A better powered human kinetic study and a kinetic study using non‐human primates, however, showed that the production rate but not the clearance of Lp(a)‐apo(a) was significantly reduced following evolocumab or alirocumab treatment, respectively . These data concur with the observation that statin treatment has no effect on Lp(a) levels despite a strongly up‐regulation of hepatic LDLR levels …”
Section: Efficacy Of Pcsk9 Inhibitors In T2dm Patientssupporting
confidence: 66%
“…These results challenge the role for PCSK9 in Lp(a) catabolism, as observed previously with PCSK9 inhibitors in human hepatocytes in vitro 14 and in nonhuman primates or healthy volunteers in vivo. 16,18 However, Lp(a)-apo(a) APR did not correlate with plasma PCSK9 concentrations, likely due to the small number of subjects. Beyond Lp(a) levels, PCSK9 inhibitors also reduce plasma apoE concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…15 In nonhuman primates, we reported that alirocumab strongly reduced the circulating Lp(a) concentration by acting on apo(a) production rate. 16 In humans, in vivo lipoprotein kinetics studies with PCSK9 monoclonal antibodies have also led to conflicting data. While alirocumab induced a nonsignificant increase in the Lp(a) FCR in one study, 17 evolocumab led to a significant decrease in the Lp(a) production rate in another one.…”
mentioning
confidence: 99%
“…However, data on the possible effect of PCSK9 on them is limited only by annexin A2 [ 24 ]. Furthermore, the results of recent studies with primates demonstrated the influence of PCSK9 inhibitors on Lp(a) production but not on catabolism [ 27 ]. An alternative mechanism might involve the elimination of circulating immune complexes formed by therapeutic MABs and PCSK9 associated with apoB100–containing lipoproteins and Lp(a), in particular [ 28 ].…”
Section: Discussionmentioning
confidence: 99%